Analyzing employee awareness towards quality at Wisma Negeri, Negeri Sembilan / Nur Fatin Bahrum and Mohd Khairani Che Johari - Bahrum, Nur Fatin; Che Johari, Mohd Khairani (2014)
The purpose of this study is to identify whether variable of reliability has a significant relationship to improve quality service in government sector; and whether variable of tangibility has a significant relationship to improve quality service in government sector; whether variable of responsiveness has a significant relationship to improve quality service in government sector; whether variable of assurance has a significant relationship to improve quality service in government sector; whether variable of empathy has a significant relationship to improve quality service in government sector at Wisma Negeri, Negeri Sembilan. Researcher has used the questionnaire to obtain information from the respondents that have been selected. There are three parts of question in the questionnaire. The first part is asking about the demographic and the second part is asking about the independent variables of the research that includes Section A, B, C, D and E. They were then distributed to 100 employees as a respondent for this research study. Later, the questionnaires were being analysed through Statistical Package for the Social Science (SPSS). Data analysis methods that has been used are frequency distribution, descriptive statistics, Cronbach’s coefficient alpha and multiple regression analysis. The study found that there is a significant relationship between empathy variable and quality service. For reliability, tangibility, responsiveness and assurance is not significant with the dependent variable. Therefore, it is suggested that more study on employee awareness towards quality service can be conducted in organization in the future.